Polyethylenenaphthalate resin composition and molded article thereof

JP2025041006APending Publication Date: 2025-03-26TEIJIN LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023148048
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

AI Technical Summary

Benefits of technology

【0008】 本発明の樹脂組成物は耐擦傷性に優れ、かつそれよりなる成形品が波長選択的な吸収特性を有し、薄肉部であっても吸収特性が維持されるポリエチレンナフタレート樹脂組成物であるため、それよりなる成形品は、自動車、産業機械、家庭用電気機械、カメラ等に搭載される赤外線センサーを覆うカバー材料として好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025041006000001
    Figure 2025041006000001
Patent Text Reader

Abstract

To provide a polyethylene naphthalate resin composition that is highly scratch-resistant and allows molded articles made from it to have wavelength-selective absorption characteristics, and to maintain these absorption characteristics even in thin-walled parts.SOLUTION: There is provided a resin composition, containing: 1 to 30 pts.wt. of (B) polybutylenenaphthalate resin (component B); and 0.055 to 1.3 pts.wt. of (C) coloring agent (component C) based on 100 pts.wt. of (A) polyethylenenaphthalate resin (component A), wherein the average value of light transmittance at 400 to 700 nm in the thickness direction of a molded article formed in thickness of 1 mm is 1.5% or less, and the average values of light transmittance at 1050 to 1100 nm in the thickness direction of the molded articles formed in thickness of 1 mm and 2 mm, respectively, are both 80% or more, and wherein the resin composition excluding laser welding applications does not include polycarbonate resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyethylene naphthalate resin composition which is excellent in abrasion resistance, and which provides a molded article made therefrom with wavelength-selective absorption characteristics, and which maintains its absorption characteristics even in thin-walled portions. [Background technology]

[0002] In recent years, factory automation has been attracting attention as a system that automates production processes to compensate for rising labor costs and labor shortages. This system replaces tasks previously performed by humans with robots to automate processes, but various sensors are essential for controlling these robots and various devices, and the demand for high-precision sensors is increasing. In the case of sensors that use light, near-infrared light with wavelengths of around 800 to 1100 nm is generally used for sensing. However, when sensing with infrared light, visible light to near-infrared light becomes noise, so a cover material is required that transmits the wavelength range used for sensing and blocks the transmission of wavelengths below that range. Glass and resin are used as cover materials, and transparent materials such as acrylic resin and polycarbonate resin are commonly used for resin. However, these transparent resins have low scratch resistance, and when placed on the exterior as a cover material, there is a problem that the surface is scratched with use, impairing the appearance and infrared transmittance, and reducing the accuracy of the sensor.

[0003] Studies on wavelength selection control resins have been conducted in the past. A technology has been disclosed in which multiple coloring agents with different absorption wavelength bands are used in combination to cut the visible light region to a part of the near infrared region. (See Patent Documents 1 and 2) However, these resin compositions are mainly composed of polycarbonate resin, and the scratch resistance is insufficient for use as a cover material. One of the other transparent resins is polyethylene naphthalate resin. Since polyethylene naphthalate resin has a slower crystallization rate in a static field than polyethylene terephthalate resin, it has the characteristic that transparent molded products can be easily obtained by injection molding, and it is used for transparent injection molded product applications. However, depending on the molding conditions, whitening may occur in the thin wall parts and gate parts of the molded product, and there is a problem in ensuring stable transparency. As a means for suppressing whitening of molded products, a method of adding polyetherimide resin to polyethylene naphthalate resin has been disclosed. (See Patent Document 3) However, no study has been conducted on the wavelength selection control and scratch resistance of these resin compositions. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-9222 A [Patent Document 2] Patent No. 6658942 [Patent Document 3] JP 2021-152133 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a polyethylene naphthalate resin composition which is excellent in abrasion resistance, and which provides a molded article made therefrom with wavelength-selective absorption characteristics, and which maintains its absorption characteristics even in thin-walled portions. [Means for solving the problem]

[0006] As a result of intensive research aimed at achieving the above-mentioned object, the inventors have discovered that by adding specific amounts of polybutylene naphthalate resin and a colorant to polyethylene naphthalate resin, it is possible to provide a polyethylene naphthalate resin composition which has excellent scratch resistance, and in which a molded article made therefrom has wavelength-selective absorption characteristics and which maintains the absorption characteristics even in thin-walled portions, thereby solving the above-mentioned problems.

[0007] That is, the present invention is as follows. 1. A resin composition, excluding laser welding applications, which contains 1 to 30 parts by weight of (B) polybutylene naphthalate resin (B component) and 0.055 to 1.3 parts by weight of (C) colorant (C component) per 100 parts by weight of (A) polyethylene naphthalate resin (A component), wherein the average light transmittance in the thickness direction of a molded product molded to a thickness of 1 mm at wavelengths of 400 to 700 nm is 1.5% or less, and the average light transmittance in the thickness direction of a molded product molded to a thickness of 1 mm and a molded product molded to a thickness of 2 mm are both 80% or more at wavelengths of 1050 to 1100 nm, and wherein the resin composition does not contain polycarbonate resin. 2. The resin composition according to item 1 above, wherein component C is at least one colorant selected from the group consisting of (C1) a colorant (component C1) having an absorption maximum at a wavelength of less than 650 nm and (C2) a colorant (component C2) having an absorption maximum at a wavelength of 650 to 880 nm. 3. The resin composition according to item 2 above, wherein component C2 is at least one colorant selected from the group consisting of anthraquinone-based colorants, phthalocyanine-based colorants, perylene-based colorants, and heterocyclic colorants. 4. The melt volume flow rate measured at 300°C and 1.2 kg was 18.0 cm 3 4. The resin composition according to any one of items 1 to 3 above, wherein the viscosity is less than 1 / 10 min. 5. The resin composition according to any one of items 1 to 4 above, wherein the area of ​​a crystallization peak upon cooling, as measured using a differential scanning calorimeter at a cooling rate of 10° C. / min, is less than 1.0 J / g. 6. A molded article obtained by molding the resin composition according to any one of items 1 to 5 above. 7. The molded article according to the preceding paragraph 6, which is a cover material covering an infrared sensor.

Advantages of the Invention

[0008] The resin composition of the present invention is excellent in scratch resistance, and the molded article made therefrom has wavelength-selective absorption characteristics, and the absorption characteristics are maintained even in a thin portion. Since it is a polyethylene naphthalate resin composition, the molded article made therefrom can be suitably used as a cover material covering an infrared sensor mounted on an automobile, an industrial machine, a household electric appliance, a camera, etc.

Modes for Carrying Out the Invention

[0009] Hereinafter, the details of the present invention will be further described.

[0010] <Regarding Component A> The polyethylene naphthalate resin, which is Component A of the present invention, can be produced using a dicarboxylic acid component mainly composed of naphthalenedicarboxylic acid and / or an ester-forming derivative of naphthalenedicarboxylic acid, and a glycol component mainly composed of ethylene glycol. By using a polyethylene naphthalate resin as Component A, high scratch resistance can be imparted.

[0011] The naphthalenedicarboxylic acid component is mainly composed of 2,6-naphthalenedicarboxylic acid and 2,7-naphthalenedicarboxylic acid, but other dicarboxylic acids can be used in combination as long as the properties are not impaired. Examples of other dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and diphenylether-4,4'-dicarboxylic acid, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, and oxalic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. One or more of these may be used, and they can be selected arbitrarily depending on the purpose. The amount of other dicarboxylic acids used is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, and particularly preferably 5 mol% or less, based on the total acid components. The ester-forming derivatives of naphthalenedicarboxylic acid are mainly composed of dimethyl 2,6-naphthalenedicarboxylate and dimethyl 2,7-naphthalenedicarboxylate, but can be used in combination with other ester-forming derivatives of dicarboxylic acids as long as the properties are not impaired. Examples of the ester-forming derivatives of other dicarboxylic acids include lower dialkyl esters of aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and diphenylether-4,4'-dicarboxylic acid, lower dialkyl esters of alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid, and lower dialkyl esters of aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, and oxalic acid. One or more of these may be used, and can be selected arbitrarily depending on the purpose. The amount of the ester-forming derivatives of other dicarboxylic acids used is preferably 30 mol % or less, more preferably 20 mol % or less, further preferably 10 mol % or less, and particularly preferably 5 mol % or less, based on the total amount of the ester-forming derivatives of dicarboxylic acids.

[0012] A small amount of a trifunctional or higher functional carboxylic acid component such as trimellitic acid may be used, or a small amount of an acid anhydride such as trimellitic anhydride may be used, or a small amount of a hydroxycarboxylic acid or an alkyl ester thereof such as lactic acid or glycolic acid may be used, and these can be selected arbitrarily depending on the purpose.

[0013] The glycol component is mainly composed of ethylene glycol, but other glycol components can be used in combination within the range that does not impair the properties. As the other glycol components, for example, one or more of alkylene glycols such as 1,4-butanediol, 1,3-propylene glycol, 1,2-propylene glycol, neopentylene glycol, hexamethylene glycol, decamethylene glycol, cyclohexanedimethanol, diethylene glycol, triethylene glycol, poly(oxy)ethylene glycol, poly(oxy)tetramethylene glycol, and poly(oxy)methylene glycol may be used, and can be arbitrarily selected depending on the purpose. Furthermore, a small amount of a polyhydric alcohol component such as glycerin may be used. Also, a small amount of an epoxy compound may be used. The amount of the other glycol components used is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, and particularly preferably 5 mol% or less, based on the total glycol components.

[0014] The polyethylene naphthalate resin can be produced by a conventionally known production method. That is, it can be produced by a direct esterification method in which a dicarboxylic acid component and a diol component are directly reacted to distill off water, followed by esterification, followed by polycondensation under reduced pressure, or by a transesterification method in which a dicarboxylic acid dimethyl ester and a diol component are reacted to distill off methyl alcohol, followed by transesterification, followed by polycondensation under reduced pressure. In order to further increase the intrinsic viscosity number, solid-phase polymerization can be carried out.

[0015] During the above transesterification reaction, esterification reaction, and polycondensation reaction, it is preferable to use a catalyst and a stabilizer. As the transesterification catalyst, Mg compounds, Mn compounds, Ca compounds, Zn compounds, Ti compounds, etc. are used. Examples include their acetates, monocarboxylates, alcoholates, and oxides. Also, the esterification reaction can be carried out only with dicarboxylic acid and diol without adding a catalyst, but it can also be carried out in the presence of the polycondensation catalyst described later. As the polycondensation catalyst, Ge compounds, Ti compounds, Sb compounds, etc. can be used. Examples include germanium dioxide, germanium hydroxide, germanium alcoholate, titanium tetrabutoxide, titanium tetraisopropoxide, and titanium oxalate. It is preferable to use a phosphorus compound as the stabilizer. Preferred phosphorus compounds include phosphoric acid and its esters, phosphorous acid and its esters, and hypophosphorous acid and its esters. Also, during the esterification reaction, a tertiary amine such as triethylamine, a quaternary ammonium hydroxide such as tetraethylammonium hydroxide, and a basic compound such as sodium carbonate can be added to suppress the by-production of diethylene glycol. Further, various stabilizers and modifiers can be blended into the obtained polyester resin.

[0016] The intrinsic viscosity of Component A is preferably 0.5 to 1.0 dl / g, more preferably 0.55 to 0.95 dl / g, and even more preferably 0.6 to 0.85 dl / g. If the intrinsic viscosity of Component A is less than 0.5 dl / g, the toughness may be inferior, and if it exceeds 1.0 dl / g, the fluidity during injection molding may be insufficient.

[0017] <Regarding Component B> The polybutylene naphthalate resin, which is Component B of the present invention, can be produced using a dicarboxylic acid component mainly composed of naphthalenedicarboxylic acid and / or an ester-forming derivative of naphthalenedicarboxylic acid, and a glycol component mainly composed of 1,4-butanediol.

[0018] The naphthalenedicarboxylic acid component is mainly composed of 2,6-naphthalenedicarboxylic acid and 2,7-naphthalenedicarboxylic acid, but other dicarboxylic acids can be used in combination as long as the properties are not impaired. Examples of other dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and diphenylether-4,4'-dicarboxylic acid, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, and oxalic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. One or more of these may be used, and can be selected arbitrarily depending on the purpose. The amount of other dicarboxylic acids used is preferably 30 mol% or less, more preferably 20 mol% or less, based on the total acid components. The ester-forming derivatives of naphthalenedicarboxylic acid are mainly composed of dimethyl 2,6-naphthalenedicarboxylate and dimethyl 2,7-naphthalenedicarboxylate, but can be used in combination with ester-forming derivatives of other dicarboxylic acids as long as the properties are not impaired. Examples of ester-forming derivatives of other dicarboxylic acids include lower dialkyl esters of aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and diphenylether-4,4'-dicarboxylic acid, lower dialkyl esters of alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid, and lower dialkyl esters of aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, and oxalic acid. One or more of these may be used, and can be selected arbitrarily depending on the purpose. The amount of the ester-forming derivatives of other dicarboxylic acids used is preferably 30 mol% or less, more preferably 20 mol% or less, based on the total dicarboxylic acid ester-forming derivative components.

[0019] A small amount of a trifunctional or higher dicarboxylic acid component such as trimellitic acid, an acid anhydride such as trimellitic anhydride, or a hydroxycarboxylic acid or an alkyl ester thereof such as lactic acid or glycolic acid may be used, and may be selected according to the purpose.

[0020] The glycol component is mainly 1,4-butanediol, but other glycol components can be used in combination within the range that does not impair the properties. As the other glycol components, for example, one or more alkylene glycols such as ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, neopentylene glycol, hexamethylene glycol, decamethylene glycol, cyclohexanedimethanol, diethylene glycol, triethylene glycol, poly(oxy)ethylene glycol, poly(oxy)tetramethylene glycol, and poly(oxy)methylene glycol may be used, and can be arbitrarily selected depending on the purpose. Furthermore, a small amount of a polyhydric alcohol component such as glycerin may be used. A small amount of an epoxy compound may also be used. The amount of the other glycol components used is preferably 30 mol% or less, more preferably 20 mol% or less, based on the total glycol components.

[0021] The amount of the glycol component used is preferably 1.1 to 1.4 times by mol relative to the dicarboxylic acid or the ester-forming derivative of the dicarboxylic acid. If the amount of the glycol component used is less than 1.1 times by mol, the esterification or transesterification reaction may not proceed sufficiently, which is not preferable. Also, if the amount exceeds 1.4 times by mol, the reaction rate may slow down, although the reason is unclear, and the amount of by-products such as tetrahydrofuran generated from the excess glycol component may increase, which is not preferable.

[0022] In the production of polybutylene naphthalate resin, a titanium compound is used as a polymerization catalyst. The titanium compound used as a polymerization catalyst is preferably a tetraalkyl titanate, specifically tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-sec-butyl titanate, tetra-t-butyl titanate, tetra-n-hexyl titanate, tetracyclohexyl titanate, tetraphenyl titanate, tetrabenzyl titanate, etc., and may be used as a mixed titanate. Among these titanium compounds, tetra-n-propyl titanate, tetraisopropyl titanate, and tetra-n-butyl titanate are particularly preferred, and tetra-n-butyl titanate is the most preferred. The amount of the titanium compound added is preferably 10 ppm or more and 60 ppm or less, more preferably 15 ppm or more and 30 ppm or less, in terms of the titanium atom content in the produced polybutylene naphthalate. If the titanium atom content in the produced polybutylene naphthalate exceeds 60 ppm, the color tone and thermal stability of the resin composition of the present invention may decrease, which is not preferable. On the other hand, if the titanium atom content is less than 10 ppm, good polymerization activity may not be obtained, and a polybutylene naphthalate resin with a sufficiently high intrinsic viscosity may not be obtained, which is not preferable. The polybutylene naphthalate resin of the present invention is preferably produced through an esterification or transesterification reaction step and a subsequent polycondensation reaction step of a dicarboxylic acid component mainly composed of naphthalenedicarboxylic acid and / or its ester-forming derivative and a glycol component mainly composed of 1,4-butanediol in the presence of a titanium compound, and the temperature at the end of the esterification or transesterification reaction is preferably in the range of 180°C to 220°C, more preferably 180°C to 210°C. If the temperature at the end of the esterification or transesterification reaction exceeds 220°C, the reaction rate increases, but by-products such as tetrahydrofuran may increase, which is not preferable. In addition, if the temperature is less than 180°C, the reaction may not proceed.The reaction product (bis glycol ether and / or its low polymer) obtained by an esterification or transesterification reaction is preferably polycondensed under a reduced pressure of 0.4 kPa (3 Torr) or less at a temperature not lower than the melting point of the polybutylene naphthalate resin and not higher than 270 °C. When the polycondensation reaction temperature exceeds 270 °C, the reaction rate rather decreases and the coloring becomes significant, which is not preferable.

[0023] By adding a polybutylene naphthalate resin having compatibility with the component A, it is possible to effectively suppress whitening in the thin-walled portion of the molded article while maintaining scratch resistance and transparency.

[0024] The content of the component B is 1 to 30 parts by weight, preferably 2 to 25 parts by weight, and more preferably 3 to 20 parts by weight with respect to 100 parts by weight of the component A. When the content of the component B is less than 1 part by weight, the light transmittance in the near-infrared region in the thin-walled portion decreases. On the other hand, when it exceeds 30 parts by weight, the scratch resistance decreases.

[0025] <Regarding the component C> The coloring agent, which is the component C of the present invention, can be selected from dyes (organic, inorganic), pigments (organic, inorganic), etc., and is not particularly limited as long as the resin composition of the present invention can be obtained. Specifically, the average light transmittance in the thickness direction of a molded product of the present invention molded to a thickness of 1 mm at a wavelength of 400 to 700 nm is 1.5% or less, and the average light transmittance in the thickness direction of a molded product of the present invention molded to a thickness of 1 mm and a molded product of the present invention molded to a thickness of 2 mm at a wavelength of 1050 to 1100 nm is both 80% or more. As one embodiment for providing such wavelength selectivity, it is preferable that the component C is at least one coloring agent selected from the group consisting of a coloring agent (component C1) having an absorption maximum at a wavelength of less than 650 nm and a coloring agent (component C2) having an absorption maximum at a wavelength of 650 to 880 nm. As the coloring agent, it is preferable to use a dye because the dye does not cause diffuse reflection on the surface of the particles. Examples of dye-based colorants include anthraquinone-based colorants, perinone-based colorants, perylene-based colorants, methine-based colorants, azo-based colorants, quinoline-based colorants, phthalocyanine-based colorants, squarylium-based colorants, and heterocyclic-based colorants, etc. Among these, anthraquinone-based colorants, phthalocyanine-based colorants, perylene-based colorants, and heterocyclic-based colorants, which have high heat resistance, are more preferred, and anthraquinone-based colorants, perylene-based colorants, and heterocyclic-based colorants are particularly preferred.

[0026] The content of component C is 0.055 to 1.3 parts by weight, preferably 0.08 to 1.0 parts by weight, and more preferably 0.1 to 0.5 parts by weight, relative to 100 parts by weight of component A. If the content of component C is less than 0.055 parts by weight, sufficient cut characteristics at wavelengths of 400 to 700 nm cannot be obtained. On the other hand, if it exceeds 1.3 parts by weight, the scratch resistance of the resin composition deteriorates.

[0027] <Characteristics of resin composition> The resin composition of the present invention has a melt volume flow rate of 18.0 cm3 measured at 300°C and 1.2 kg. 3 / 10min or less is preferable, and 16.0cm 3 / 10min or less is more preferable, and 14.0cm3 It is particularly preferable that the melt volume flow rate is less than 5.0 cm / 10 min. 3 The melt volume flow rate is expressed as the volume of the sample extruded in 10 minutes according to JIS K 7210. 3 If the melt volume flow rate exceeds 100 / min, the scratch resistance may decrease. The method for adjusting the melt volume flow rate is not particularly limited, but it can be achieved, for example, by appropriately adjusting the blending ratio of the A component, the B component, and the C component, the screw rotation speed during melt kneading, the discharge amount, the molding temperature, and the kneading time.

[0028] The resin composition of the present invention preferably has a crystallization peak area of ​​less than 1.0 J / g, more preferably less than 0.5 J / g, and even more preferably less than 0.2 J / g, measured at a temperature drop rate of 10° C. / min using a differential scanning calorimeter, and particularly preferably has no crystallization peak of less than 1.0 J / g. Resin compositions with a crystallization peak area of ​​more than 1.0 J / g are prone to whitening due to oriented crystallization, and the light transmittance in the near infrared region in the thin wall portion may decrease. The means for achieving the above are not particularly limited, but can be achieved by appropriately adjusting the molecular weight of the A component and B component used, the type and content of the transesterification catalyst, polymerization catalyst, and stabilizer contained, the polymerization reaction conditions, and the method for cleaning the polymerization reaction tank. The area of ​​the cooling crystallization peak referred to here refers to the area of ​​the exothermic peak appearing on the heat flow curve in the range of 130 to 250°C when 4 to 7 mg of the resin composition is heated from 25 to 35°C at a heating rate of 20°C / min to 300°C, held isothermal for 5 minutes, rapidly cooled to 25 to 35°C at a heating rate of 100°C / min or more, heated again to 300°C at a heating rate of 10°C / min, held isothermal for 5 minutes, and cooled to 25 to 35°C at a cooling rate of 10°C / min.

[0029] (Other ingredients) The resin composition of the present invention does not substantially contain polycarbonate resin. The term "substantially does not contain" means that the content of polycarbonate resin is 0.3 parts by weight or less per 100 parts by weight of component A. The polycarbonate resin referred to here is obtained by reacting a dihydric phenol with a carbonate precursor, and refers to a high molecular weight substance having a carbonate bond in the main chain. The dihydric phenol used is not particularly limited, and a representative example is bisphenol A. If the resin composition contains polycarbonate resin, the scratch resistance is deteriorated. The resin composition of the present invention may contain various additives such as an antioxidant and a mold release agent, provided such additives are not contrary to the spirit of the present invention.

[0030] <Antioxidants> The resin composition of the present invention may contain at least one antioxidant selected from the group consisting of hindered phenol compounds, phosphite compounds, phosphonite compounds, and thioether compounds. The incorporation of an antioxidant not only stabilizes the color and fluidity during molding, but also has the effect of improving hydrolysis resistance.

[0031] The content of the antioxidant is preferably 0.01 to 2 parts by weight, more preferably 0.03 to 1 part by weight, and even more preferably 0.05 to 0.5 parts by weight, based on 100 parts by weight of component A. If the content of the antioxidant is less than 0.01 part by weight, the antioxidant effect is insufficient, and not only the color and fluidity during molding processing become unstable, but also the hydrolysis resistance may deteriorate. If the content is more than 2 parts by weight, reactive components derived from the antioxidant may actually deteriorate the hydrolysis resistance.

[0032] It is also preferable to use the above-mentioned hindered phenol compound in combination with any two or more of a phosphite compound, a phosphonite compound, or a thioether compound. By using the hindered phenol compound in combination with any two or more of a phosphite compound, a phosphonite compound, or a thioether compound, a synergistic effect as a stabilizer is exhibited, which is effective in stabilizing the color and fluidity during molding and improving the hydrolysis resistance.

[0033] <Method of producing resin composition> Any method can be used to produce the resin composition of the present invention. For example, each component and optionally other components can be premixed, then melt-kneaded, and pelletized. Premixing means can include a Nauta mixer, a V-type blender, a Henschel mixer, a mechanochemical device, an extrusion mixer, and the like. In premixing, granulation can be performed using an extrusion granulator or a briquetting machine, etc. After premixing, the mixture is melt-kneaded using a melt kneader such as a vented twin-screw extruder, and pelletized using a pelletizer or other device. Other examples of melt kneaders include a Banbury mixer, a kneading roll, a thermostatic stirring vessel, and the like, but a vented twin-screw extruder is preferred. Alternatively, each component and optionally other components can be independently supplied to a melt kneader such as a twin-screw extruder without premixing.

[0034] <About the molded body> The molded article made of the resin composition of the present invention can be obtained by molding the pellets produced as described above. It is preferably obtained by injection molding or extrusion molding. Injection molding can be performed not only by ordinary molding methods, but also by injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including a method of injecting a supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, multi-color molding, sandwich molding, and ultra-high speed injection molding. In addition, molding can be performed by either the cold runner method or the hot runner method. In extrusion molding, a molded article can be obtained by extruding a round bar and then cutting it into a disk shape, or by extruding a thick sheet and then punching it into a predetermined shape. EXAMPLES

[0035] The following examples are provided to illustrate the present invention, but are not intended to limit the scope of the invention. Physical properties were evaluated by the following methods.

[0036] [Evaluation of resin composition] (1) Scratch resistance The pellets obtained by the method described below were dried at 160°C for 5 hours, and then injection molded using an injection molding machine (EC130SXII-4Y, manufactured by Toshiba Machine Co., Ltd.) under conditions of a cylinder temperature of 305°C and a mold temperature of 80°C to obtain a plate-shaped test piece with a thickness of 2 mm, width and length of 50 mm. A sliding test was performed on this test piece using a reciprocating friction tester (Tribogear TYPE-40, manufactured by Shinto Scientific Co., Ltd.) under conditions of a load of 0.5 kg, a speed of 100 mm / s, and 1500 reciprocations, with a SUS304 metal ball with a diameter of 10 mm covered with canvas as an indenter. The arithmetic mean roughness Ra of the sliding surface after the test was obtained in the direction perpendicular to the sliding direction according to JIS-01 / 13 using a surface roughness shape measuring instrument (SURFCOM NEX001 SD2-12, manufactured by Tokyo Seimitsu Co., Ltd.). The test was performed three times, and the average value was used as an index of the scratch resistance of the composition. The arithmetic mean roughness must be 0.15 μm or less.

[0037] (2)Light transmittance The pellets obtained by the method described below were dried at 160°C for 5 hours, and then injection molded using an injection molding machine (Toshiba Machine Co., Ltd., EC130SXII-4Y) under conditions of a cylinder temperature of 305°C and a mold temperature of 80°C to obtain plate-shaped test pieces with thicknesses of 1 mm and 2 mm, widths of 50 mm, and lengths of 25 mm. The test pieces were measured for spectral light transmittance in the wavelength range of 300 to 2500 nm at 1 nm intervals using an ultraviolet-visible-near infrared spectrophotometer (V-770, JASCO Corporation). From the obtained spectral spectrum, the average values ​​of light transmittance in the wavelength range of 400 to 700 nm and wavelengths of 1050 to 1100 nm were calculated.

[0038] (3) Melt Volume Flow Rate Using the pellets obtained by the method described below, measurements were carried out in accordance with JIS K 7210 under conditions of 300° C. and 1.2 kg.

[0039] (4) Area of ​​crystallization peak during cooling Using a differential scanning calorimeter (NETZSCH DSC214), 4 to 7 mg of pellets obtained by the following method were heated from 25 to 35 ° C. to 300 ° C. at a heating rate of 20 ° C. / min, held at isothermal temperature for 5 minutes, rapidly cooled to 25 to 35 ° C. at a rate of 100 ° C. / min or more, heated again to 300 ° C. at a heating rate of 10 ° C. / min, held at isothermal temperature for 5 minutes, and cooled to 25 to 35 ° C. at a cooling rate of 10 ° C. / min. The area of ​​the exothermic peak appearing on the heat flow curve in the range of 130 to 250 ° C. was determined. In addition, when no exothermic peak was observed, it was recorded as ND.

[0040] [Examples 1-11, Example 13, Comparative Examples 1-5] According to the contents shown in Table 1, the mixture of components A and B using a tumbler and component C were fed into a twin-screw extruder from the first feed port, and pelletized by melt kneading extrusion at a temperature of 300°C and a screw rotation speed of 200 rpm. Here, the first feed port refers to the feed port at the base. The twin-screw extruder used was a vented twin-screw extruder with a diameter of 30 mm (TEX30α-31.5BW-2V, manufactured by Japan Steel Works, Ltd.).

[0041] [Example 12] The mixture was melt-kneaded, extruded and pelletized in the same manner as in Example 1, except that the screw rotation speed of the twin-screw extruder was set to 300 rpm.

[0042] [Reference example 1] The mixture was melt-kneaded, extruded and pelletized in the same manner as in Example 1, except that the extrusion temperature of the twin-screw extruder was set to 280°C.

[0043] The following materials were used in the examples and comparative examples of the present invention. (Component A) A-1: Polyethylene naphthalate resin obtained in Production Example I <Manufacturing example I> 100 parts by weight of dimethyl naphthalenedicarboxylate and 60 parts by weight of ethylene glycol were subjected to an ester exchange reaction in the presence of 0.010 parts by weight (10 mmol%) of cobalt acetate tetrahydrate and 0.030 parts by weight (30 mmol%) of manganese acetate tetrahydrate by a conventional method, 0.012 parts by weight (10 mmol%) of antimony trioxide was added 20 minutes after distillation of methanol, and 0.020 parts by weight (50 mmol%) of orthophosphoric acid was added before the end of the ester exchange reaction, followed by polycondensation reaction at 295°C under high vacuum to obtain a polyethylene naphthalate resin with an intrinsic viscosity of 0.51 dl / g. The obtained polyethylene naphthalate resin was subjected to solid-phase polymerization at a temperature of 227°C and a vacuum degree of 0.5 Torr for 8 hours to obtain a polyethylene naphthalate resin with an intrinsic viscosity of 0.68 dl / g. A-2: Polyethylene naphthalate resin obtained in Production Example II <Manufacturing example II> 100 parts by weight of dimethyl naphthalenedicarboxylate and 60 parts by weight of ethylene glycol were subjected to an ester exchange reaction in the presence of 0.010 parts by weight (10 mmol%) of cobalt acetate tetrahydrate and 0.036 parts by weight (36 mmol%) of manganese acetate tetrahydrate by a conventional method, 0.027 parts by weight (23 mmol%) of antimony trioxide was added 20 minutes after distillation of methanol, and 0.020 parts by weight (50 mmol%) of orthophosphoric acid was added before the end of the ester exchange reaction, followed by polycondensation reaction at 295°C under high vacuum to obtain a polyethylene naphthalate resin with an intrinsic viscosity of 0.50 dl / g. The obtained polyethylene naphthalate resin was subjected to solid-phase polymerization at a temperature of 227°C and a vacuum degree of 0.5 Torr for 8 hours to obtain a polyethylene naphthalate resin with an intrinsic viscosity of 0.62 dl / g. A-3 (Comparative Example): Polycarbonate resin: Panlite L-1225WX (Teijin Limited, viscosity average molecular weight: 19,700)

[0044] (B component) B-1: Polybutylene naphthalate resin obtained in Production Example III <Production example III> 315.0 parts of 2,6-naphthalenedicarboxylic acid dimethyl ester, 200.0 parts of 1.4-butanediol, and 0.062 parts of tetra-n-butyl titanate were placed in an ester exchange reaction tank, and the ester exchange reaction was carried out for 150 minutes while the temperature of the ester exchange reaction tank was raised to 210°C. The reaction product obtained was then transferred to a polycondensation reaction tank to start the polycondensation reaction. The polycondensation reaction was carried out by gradually reducing the pressure in the polycondensation reaction tank from normal pressure to 0.13 kPa (1 torr) or less over 40 minutes, and at the same time raising the temperature to a predetermined reaction temperature of 260°C. Thereafter, the polycondensation reaction was carried out for 140 minutes while maintaining the polycondensation reaction temperature at 260°C and the pressure at 0.13 kPa (1 torr). When 140 minutes had passed, the polycondensation reaction was terminated, and the polybutylene naphthalate resin was extracted in the form of strands, which were then cut into chips using a cutter while being cooled with water. Next, the obtained polybutylene naphthalate resin was subjected to solid-phase polymerization for 8 hours under conditions of a temperature of 213° C. and a pressure of 0.13 kPa (1 Torr) or less, to obtain a polybutylene naphthalate resin having an intrinsic viscosity of 1.05 dl / g.

[0045] (C1 component) C1-1: NUBIAN BLACK PC-5857 (Orient Chemical Industries, Ltd., maximum absorption wavelength 599 nm) (C2 component) C2-1: Phthalocyanine colorant FDR-004 (Yamada Chemical Industry Co., Ltd., maximum absorption wavelength 720 nm) C2-2: Anthraquinone colorant SDO-7 (Arimoto Chemical Industry Co., Ltd., maximum absorption wavelength 676 nm) C2-3: Anthraquinone colorant SDO-11 (Arimoto Chemical Industry Co., Ltd., maximum absorption wavelength 761 nm) C2-4: Heterocyclic colorant SDO-C33 (Arimoto Chemical Industry Co., Ltd., maximum absorption wavelength 847 nm) C2-5: Perylene-based colorant Lumogen IR-765 (BASF Japan Ltd., maximum absorption wavelength 769 nm)

[0046] [Table 1]

[0047] <Examples 1 to 13> Because the composition is within the scope of the present invention, it is possible to obtain a molded article that has excellent scratch resistance, wavelength-selective absorption properties, and maintains its absorption properties even in thin-walled portions. <Comparative Example 1> Since the content of component B was below the lower limit, the average light transmittance at a wavelength of 1050 to 1100 nm at a thickness of 1 mm was low. <Comparative Example 2> Since the content of component B exceeded the upper limit, the scratch resistance was poor. <Comparative Example 3> Since the content of component C was below the lower limit, the average light transmittance at wavelengths of 400 to 700 nm was high. <Comparative Example 4> Since the content of component C exceeded the upper limit, the scratch resistance was poor. <Comparative Example 5> Since the resin composition contained a polycarbonate resin, the results showed poor scratch resistance. <Reference example 1> Since component A is a polycarbonate resin, the result was poor in scratch resistance.

Claims

1. A resin composition, excluding those for laser welding applications, which contains 1 to 30 parts by weight of (B) polybutylene naphthalate resin (B component) and 0.055 to 1.3 parts by weight of (C) coloring material (C component) per 100 parts by weight of (A) polyethylene naphthalate resin (A component), wherein the average light transmittance in the thickness direction of a molded product molded to a thickness of 1 mm at wavelengths of 400 to 700 nm is 1.5% or less, and the average light transmittance in the thickness direction of a molded product molded to a thickness of 1 mm and a molded product molded to a thickness of 2 mm at wavelengths of 1050 to 1100 nm are both 80% or more,

2. The resin composition according to claim 1, wherein the C component is at least one colorant selected from the group consisting of (C1) a colorant (C1 component) having an absorption maximum at a wavelength of less than 650 nm and (C2) a colorant (C2 component) having an absorption maximum at a wavelength of 650 to 880 nm.

3. 3. The resin composition according to claim 2, wherein the component C2 is at least one colorant selected from the group consisting of anthraquinone-based colorants, phthalocyanine-based colorants, perylene-based colorants, and heterocyclic colorants.

4. The melt volume flow rate measured at 300°C and 1.2 kg was 18.0 cm 3 The resin composition according to any one of claims 1 to 3, characterized in that the viscosity is less than 100 s / 10 min.

5. 4. The resin composition according to claim 1, wherein the area of ​​a crystallization peak upon cooling measured at a temperature-lowering rate of 10° C. / min using a differential scanning calorimeter is less than 1.0 J / g.

6. A molded article obtained by molding the resin composition according to any one of claims 1 to 3.

7. 7. The molded article according to claim 6, which is a cover material for covering an infrared sensor.

Citation Information

Patent Citations

  • Polycarbonate resin composition and filter for infrared laser

    JP2008009222A

  • Molding composed of polyethylenenaphthalate resin composition

    JP2021152133A

  • Resin composition, molded article, optical layer, cover member, and mobile body

    JP6658942B1